Perlindungan Hukum Terhadap Konsumen Dalam Transaksi E-Commerce di Media Sosial Facebook - Sapulette, Mariska Zefanya; Pesulima, Theresia Louize; Labetubun, Muchtar Anshary Hamid (PATTIMURA Law Study Review, 2024)
Online buying and selling is carried out by someone through various private social media channels, therefore online buying and selling is directly connected to sellers and buyers. One of the social media used for online buying and selling is Facebook, however in buying and selling via Facebook there are still problems where there is a lot of fraud because online buying and selling activities do not involve face-to-face activity between buyers and sellers. Online buying and selling agreements are also regulated in Article 5 and Article 6 of Law Number 11 of 2008 concerning Information and Electronic Transactions, hereinafter referred to as the ITE Law, which states that information, documents and electronic signatures can be valid evidence in buying and selling transactions. Online is considered valid as long as the information contained therein can be accessed, displayed, its integrity is guaranteed, and can be accounted for so that it explains a situation. The type of research used is a type of normative research which is carried out by examining library materials or secondary data, legal materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. The procedure for collecting legal materials is carried out by examining legal materials, compiling legal materials, systematic legal materials and finally processing and analyzing legal materials. The research results show that the responsibility of business actors towards consumer rights is regulated in article 19 of Law Number 8 of 1999 concerning Consumer Protection and as well as other legal protections in transactions on social media in online buying and selling as regulated in Law Number 11 2008 concerning Information and Electronic Transactions (hereinafter referred to as the ITE Law) as amended by Law Number 19 of 2016.